NEOGENE TO QUATERNARY STRESS FIELD EVOLUTION IN LESSER CAUCASUS AND ADJACENT REGIONS USING FAULT KINEMATICS ANALYSIS AND VOLCANIC CLUSTER DATA - Avagyan A.; Melkonyan R.; Sosson M.; Rolland Y.; Philip H.; Karakhanian A.; Davtyan V.; Rebaï S. (My University, 2005)
In the Great Caucasus, the Lesser Caucasus and Eastern Turkey, the distribution of Neogene to Quaternary volcanic cluster geometries, paleo-stress field data of the Lesser Caucasus area (Republic of Armenia) and the P axes of earthquakes focal mechanisms show the scale and time variability of the stress field since the beginning of the Arabia-Eurasian collision. In addition to the general N-S compression orientation, two other NW-SE and NE-SW secondary orientations are observed. Both orientations were successively significant for some period of tectonic activity. The first one was dominant between the Paleogene and the end of the Lower Miocene and the second one has prevailed between the Upper Miocene and the Quaternary. On a regional scale the principal stress axes orientations are mainly controlled by the Arabian-Eurasian plate convergence and have changed with time. Local stress orientations have been significantly influenced by secondary blocks motions and their geometries.
Keywords: Quaternary; Neogene; Cenozoic::Quaternary; Cenozoic::Neogene